Implementation of elements of the dual education system based on the interaction of the university and the school - Seytalieva Алима; Shyndaliev Нұржан (Рroblems of engineering and professional education, 2023)
The need to implement the state policy of the country’s transition to an innovative path of development implies significant changes in the system of higher education. To date, potential employers and educational institutions have come to a consensus that the modern labor market needs highly qualified specialists of a new formation, ready for any challenges that arise in front of them in an increasingly competitive environment. There is a serious problem of inconsistency of interests of production, universities and graduates of higher educational institutions regarding employment and career growth. There is a gap between the needs of production in the relevant competencies of university graduates and the offer of competencies that the university forms in accordance with the state educational standard. Therefore, this article discusses the solution of the resulting problems with the use of elements of a dual learning system with the definition of continuity between the university and the school in the specialty of Computer Science.